2020
DOI: 10.1186/s12974-020-02015-9
|View full text |Cite
|
Sign up to set email alerts
|

NOD1/RIP2 signalling enhances the microglia-driven inflammatory response and undergoes crosstalk with inflammatory cytokines to exacerbate brain damage following intracerebral haemorrhage in mice

Abstract: Background Secondary brain damage caused by the innate immune response and subsequent proinflammatory factor production is a major factor contributing to the high mortality of intracerebral haemorrhage (ICH). Nucleotide-binding oligomerization domain 1 (NOD1)/receptor-interacting protein 2 (RIP2) signalling has been reported to participate in the innate immune response and inflammatory response. Therefore, we investigated the role of NOD1/RIP2 signalling in mice with collagenase-induced ICH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…The neuroinflammatory mechanisms include activation of microglia, the resident macrophages in the brain, and other blood-derived immune cells ( 9 ). Activated microglia/macrophages and peripheral blood-derived immune cells release proinflammatory cytokines, including tumor necrosis factor (TNF-) α, interleukin (IL-) 1β, chemokines, free radicals, and other toxic chemicals, which ultimately leads to brain edema and neuronal death ( 17 , 18 ). ICH-induced neuronal death was initially divided into two different categories, necrosis and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The neuroinflammatory mechanisms include activation of microglia, the resident macrophages in the brain, and other blood-derived immune cells ( 9 ). Activated microglia/macrophages and peripheral blood-derived immune cells release proinflammatory cytokines, including tumor necrosis factor (TNF-) α, interleukin (IL-) 1β, chemokines, free radicals, and other toxic chemicals, which ultimately leads to brain edema and neuronal death ( 17 , 18 ). ICH-induced neuronal death was initially divided into two different categories, necrosis and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…RIP2 plays an important role in innate and adaptive immunity (Jaafar et al 2018). In primary microglia, RIP2 inhibition partially alleviated intracerebral haemorrhage-induced brain injury by reducing microglia activation (Wang et al 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…In the hippocampus, these cells are an important source of neurotrophic factors that contribute to neurogenesis [ 78 ]. Interestingly, it has been shown that LPS activates microglia and induces neurotrophic factors release [ 62 , 79 82 ]. However, in our model, CBD pretreatment might have prevented LPS-induced microglia activation, which could explain why the cannabinoid prevented the increase of the evaluated neurotrophic factors and cytokines levels in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%